(3OQGSI MGdGJ aj JSjjQ GdehGQO GdHTQjI s - (3QbGe(B, (3djfOIs ((3GdLRGFQs (3OGQ GdHGMK ddfTQ hGdGTgGQs, 2022)
(3LGAJ eMJhjGJ gPG GdcJGH dJhVM eGgjI GdMGdI hefgLjI eYGdLJgG aj aUdjf eJJGdjjf(B.(3Ke JWQbJ HbjI GdaUhd Edi (B20 (3MGdI eY MdhdgG ef gPg GdMGdGJ eGgh hLjR HSjW hBNQ Whjd eYbO dJJfGhd CfTWI GOGQI GdehGQO GdHTQjI aj GdefXeGJ hYQV GdaUd GdCNjQ ef GdcJGH MGdGJ GQJCjfG CfgG PGJ YdGbI hKjbI HGdehGQO GdHTQjI(B.s
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQI GdYGeIs; (3JSjjQ GdehGQO GdHTQjIs